(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
This work reports one-dimensional simulation-based analysis of the performance of thin-film solar cells using Copper Indium Gallium Selenide (CIGS) as the absorber layer. The study focuses on how three key parameters; absorber layer thickness, band gap energy and operating temperature influence the efficiency of solar cells. Simulations were performed using SCAPS-1D under standard illumination conditions (AM1.5G, 1000 W/m). The absorber layer thickness was varied from 0.8 m to 2.0 m, the band gap from 0.8 eV to 1.8 eV and the temperature from 240 K to 360 K. Results show that an optimal combination of these parameters; CIGS thickness of 1.6 m, band gap of 1.4 eV and operating temperature of 240 Kyields a maximum conversion efficiency of 19.95%. The trends indicate that increasing thickness and band gap improve efficiency up to a limit, beyond which recombination or reduced light absorption lowers performance. Similarly, higher temperatures result in efficiency loss due to increased carrier recombination. These findings provide insight into absorber layer design and optimization for improving the performance of thin-film CIGS solar cells.